A common inversion under selection in Europeans. - Stefansson, H; Helgason, A; Thorleifsson, G; Steinthorsdottir, V; Masson, G; Barnard, J; Baker, A; Jonasdottir, A; Ingason, A; Gudnadottir, V; Desnica, N; Hicks, A; et al. (2005)
A refined physical map of chromosome 17q21.31 uncovered a 900-kb inversion polymorphism. Chromosomes with the inverted segment in different orientations represent two distinct lineages, H1 and H2, that have diverged for as much as 3 million years and show no evidence of having recombined. The H2 lineage is rare in Africans, almost absent in East Asians but found at a frequency of 20% in Europeans, in whom the haplotype structure is indicative of a history of positive selection. Here we show that the H2 lineage is undergoing positive selection in the Icelandic population, such that carrier females have more children and have higher recombination rates than noncarriers.